Fostering teachers' autonomous motivation during professional learning: a self-determination theory perspective. Issue 3 (3rd July 2019) - Power, Keith; Goodnough, Karen
Abstract: Employing a self-determination theory lens, this qualitative case study analyzed the impact of a science, technology, engineering, and mathematics professional learning program on six elementary schoolteachers' autonomous motivation. The outcomes revealed that the program was successful in accommodating the teachers' needs to feel competent, related, and autonomous. The teachers reported that the program supported their volitional will to engage in self-directed learning by offering them choice, encouragement, and constructive feedback. The teachers were also provided with ample time and resources to enhance their instructional knowledge and showcase their new skills. Moreover, the teachers were able to strengthen existing relationships and expand their professional community. These relationships provided additional support for the teachers and contributed to their growth and development.